2016
DOI: 10.1016/j.cmet.2016.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Replication Defects Disturb Cellular dNTP Pools and Remodel One-Carbon Metabolism

Abstract: Mitochondrial dysfunction affects cellular energy metabolism, but less is known about the consequences for cytoplasmic biosynthetic reactions. We report that mtDNA replication disorders caused by TWINKLE mutations-mitochondrial myopathy (MM) and infantile onset spinocerebellar ataxia (IOSCA)-remodel cellular dNTP pools in mice. MM muscle shows tissue-specific induction of the mitochondrial folate cycle, purine metabolism, and imbalanced and increased dNTP pools, consistent with progressive mtDNA mutagenesis. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

36
257
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 243 publications
(300 citation statements)
references
References 53 publications
36
257
0
Order By: Relevance
“…Recent studies have shown that disruption of mitochondrial energy metabolism can cause an imbalance of ribonucleotides, which then contributes to neurodegeneration (Fasullo and Endres 2015; Nikkanen et al 2016). Deficient mitochondrial energy production makes Drosophila photoreceptors more vulnerable to light-induced degeneration and produces a visual defect in zebrafish (Taylor et al 2004; Jaiswal et al 2015).…”
Section: 4 Discussionmentioning
confidence: 99%
“…Recent studies have shown that disruption of mitochondrial energy metabolism can cause an imbalance of ribonucleotides, which then contributes to neurodegeneration (Fasullo and Endres 2015; Nikkanen et al 2016). Deficient mitochondrial energy production makes Drosophila photoreceptors more vulnerable to light-induced degeneration and produces a visual defect in zebrafish (Taylor et al 2004; Jaiswal et al 2015).…”
Section: 4 Discussionmentioning
confidence: 99%
“…This is called the cell danger hypothesis 8. Aspects of the cell danger response (CDR) are also referred to as the integrated stress response 9, 10, 11. Preclinical studies showed that the cell danger response in mice produced a treatable metabolic syndrome that was maintained by purinergic signaling.…”
Section: Introductionmentioning
confidence: 99%
“…The formulation of the cell danger hypothesis was based on the recognition that similar metabolic pathways were coordinately regulated as an adaptive response to cellular threat regardless of whether the perturbation was caused by a virus,15 a bacterium,16 genetic forms of mitochondrial disease,10 or neurodevelopmental disorders with complex gene–environment pathogenic mechanisms like autism 17. These metabolic pathways traced to mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…We enriched three of the four major enzymes in the mitochondrial folate pathway (SHMT2, MTHFD2, MTHFD1L, ALDH1L2) (Nilsson et al, 2014) (Figure 2C). Although SHMT2 was already a known nucleoid protein (Anderson et al, 2011; Bogenhagen et al, 2008; Wang and Bogenhagen, 2006) and MTHFD1L is upregulated in mouse models with mtDNA replication defects (Nikkanen et al, 2016), our dataset newly connects ALDH1L2 and MTHFD1L to mtDNA. Perhaps these enzymes in the folate cycle, which contribute to nucleotide synthesis, enable crosstalk between mtDNA replication status and cellular dinucleotide triphosphate pools.…”
Section: Discussionmentioning
confidence: 86%